Top:
x / (x + 1) - 1 / x
= [x^2 - (x +1)] / x(x+1)
= (x^2 - x - 1 ) / x (x+1)
Bottom:
x / (x + 1) + 1 / x
= [x^2 + (x +1)] / x(x+1)
= (x^2 + x + 1 ) / x (x+1)
Now you have:
(x^2 - x - 1 ) / x (x+1)
----------------------------
(x^2 + x + 1 ) / x (x+1)
= (x^2 - x - 1 ) / x (x+1) * x (x+1) / (x^2 + x + 1 )
= (x^2 - x - 1 ) /(x^2 + x + 1 )
Answer:
x^2 - x - 1
---------------------
x^2 + x + 1
30
6 times 5 is 30 and since its 6 per hour you just do it to five :)
Answer:
q .no d
Step-by-step explanation:
64p^3+125
4p^3+ 5^3
(4p+ 5 ) ( 4p^2- 4p *5 + 5^2)
(4p+5) (16p- 20p+ 25)
Answer:
=−24 hope this helps!!
Step-by-step explanation: